2012
DOI: 10.5194/cp-8-59-2012
|View full text |Cite
|
Sign up to set email alerts
|

Pollen, vegetation change and climate at Lake Barombi Mbo (Cameroon) during the last ca. 33 000 cal yr BP: a numerical approach

Abstract: Abstract. This paper presents quantitative reconstructions of vegetation and climate along the pollen sequence of Lake Barombi Mbo, southwestern Cameroon (4 • 39 45.75 N, 9 • 23 51.63 E, 303 m a.s.l.) during the last 33 000 cal yr BP, improving previous empirical interpretations. The biomisation method was applied to reconstruct potential biomes and forest successional stages. Mean annual precipitation, mean annual potential evapotranspiration and an index of moisture availability were reconstructed using mode… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 67 publications
0
35
0
Order By: Relevance
“…The transition from arid (glacial) to humid (Holocene) climate occurred between 18.5 and 15.5 cal. kyr bp in west‐central Africa, as recorded by the rise of lake level at Lake Bosumtwi (Shanahan et al ., ), the increase of fluvial activity in the Gulf of Guinea (Lézine et al ., ; Weldeab et al ., ; Kim et al ., ; Sangen et al ., ) and forest expansion in the equatorial lowlands (Maley & Brenac, ; Lebamba et al ., ). This timing matches the Bambili record, which shows that the local forest was extremely reduced during the terminal last glacial period, and started to expand in two steps dated at 18.4 and 15.5 cal.…”
Section: Discussionmentioning
confidence: 99%
“…The transition from arid (glacial) to humid (Holocene) climate occurred between 18.5 and 15.5 cal. kyr bp in west‐central Africa, as recorded by the rise of lake level at Lake Bosumtwi (Shanahan et al ., ), the increase of fluvial activity in the Gulf of Guinea (Lézine et al ., ; Weldeab et al ., ; Kim et al ., ; Sangen et al ., ) and forest expansion in the equatorial lowlands (Maley & Brenac, ; Lebamba et al ., ). This timing matches the Bambili record, which shows that the local forest was extremely reduced during the terminal last glacial period, and started to expand in two steps dated at 18.4 and 15.5 cal.…”
Section: Discussionmentioning
confidence: 99%
“…For example, landscape-scale fires of low intensity (Baker and Bunyavejchewin, 2009) or region-wide tree mortality following extreme drought events (Nepstad et al, 2007; Allen et al, 2010) are both extensive disturbances with highly heterogeneous patterns of tree mortality and subsequent recruitment. A few studies have demonstrated the occurrence of severe and broad disturbances in tropical forests on a millennial time scale, through genetic analyses and pollen research (e.g., Daïnou et al, 2010; Lebamba et al, 2012). Forest monitoring studies on the other hand are unlikely to capture the dynamics caused by infrequent severe and/or large-scale disturbances because they are generally conducted in small permanent plots for several decades (e.g., Baker et al, 2004; Clark et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Lake Barombi Mbo is located at latitude 4°39ʹ45.75" N, and longitude 9°23ʹ51.63" E, in Kumba, South West Region of Cameroon (Lebamba, Vincens, & Maley, 2012) at an elevation of 301 m asl and is about 60 km NNE of the 4100 m high active Mt. Cameroon strato volcano (Fonge, 2004).…”
Section: Description Of Study Areamentioning
confidence: 99%